EKSISTENSI BANTUAN HUKUM TERHADAP PRAJURIT TNI SEBAGAI PELAKU TINDAK PIDANA DAN PRAKTIKNYA - Tumbur Palti D. Hutapea (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
Legal assistance is an assistance given by an expertise in law area or legal advisors to those who have legal problems at every stage of investigation both outside and inside the court. The role of legal assistance for Indonesian National Armed Forces personnel is important. The Legislation covering legal assistance in the Indonesian National Armed Forces community throughout the history has prioritized internal legal assistance where the personnel itself does not have certification/ accreditation for it. The external is hard to get involve and have to obtain special permission from the Officers hand the case (Papera). Accelerating the Bill on Military Justice to revise the rules on providing legal assistance to Army personnel is priority. Furthermore, the necessary freedom to choose and establish legal assistance services of a professional advocate or by means POSBAKUM, especially cases which threatened the death penalty and additional penalty in the form of dismissal from military service.Keywords: military court, legal assistance, papera, posbakum